Investigation on the Effects of Acoustic Liner Variation and Geometry Discontinuities on the Acoustic Performance of Lined Ducts - DHIEF, Raja; MAKNI, Amine; TAKTAK, Mohamed; CHAABANE, Mabrouk; HADDAR, Mohamed (Archives of Acoustics, 2020)
Noise reduction inside waveguide systems has gained momentum owing to a great interest in it. To attenuate the sound in a broad frequency range, this study aims to compare the effects of two acoustic liners, a perforated plate backed by an air cavity (PP-Air cavity), or by a porous material (PP-PM), on the acoustic behaviour of lined ducts using a numerical model to compute the multimodal scattering matrix. From this matrix, the reflection and the transmission coefficients are computed and therefore the acoustic power attenuation is deduced. Moreover, the effects of geometry of ducts with and without changes in the section are investigated. The numerical results are obtained for five configurations, including cases of narrowing and widening of a duct portion with sudden or progressive discontinuities. Accordingly, numerical coefficients of reflection and transmission as well as the acoustic power attenuation show the relative influence of acoustic liners in each type of configuration.